From Paper to Platform: How Digitalization is Driving the Transformation of Morocco’s Tax System (International Journal of Applied Research in Management and Economics, 2025)
The digital transformation of tax administration is increasingly recognized as a strategic lever for improving governance, transparency, and efficiency in public finance management. This study examines the case of Morocco, a middle-income country that has progressively introduced digital tools such as e-filing, e-payment, and pilot initiatives for electronic invoicing within its tax system. Using a qualitative research design, the study combines insights from thirty semi-structured interviews with tax officials, business representatives, accountants, and taxpayers, alongside a comprehensive document analysis. The findings reveal significant progress in streamlining administrative processes and enhancing taxpayer trust, particularly among larger enterprises and accounting professionals. However, persistent challenges remain, notably regarding digital literacy barriers, system navigation for smaller businesses and micro-entrepreneurs, and concerns over data privacy and cybersecurity. The study also identifies cautious optimism among stakeholders regarding the potential use of emerging technologies, such as artificial intelligence and data analytics, to further improve compliance and efficiency. The Moroccan experience highlights the importance of a balanced and inclusive approach to digital tax reforms and offers practical insights for other emerging economies pursuing similar modernization efforts.